Changes in air pollution and attitude to fireworks in Beijing. (15th June 2020) - Lai, Yonghang; Brimblecombe, Peter
Abstract: Fireworks used in both public and private displays can cause brief, but extraordinarily high levels of airborne particulate matter. New Year festivities in China, have for many years led to sharp spikes in air pollution just after midnight. Potential health impacts and broader environmental concerns have resulted in increasingly stringent regulation of fireworks. While in the past these have been ineffective because of mercantile and stakeholder pressures to retain the celebratory use of fireworks, regulations are now more widely enforced. Measurements of fine particulate matter show considerable year-to-year variation, with the presence of inversions an important determinant of the firework-derived spike in the early morning on New Year's Day. Nevertheless, overall improvements are evident in recent years (2017–2019), although these are more dramatic for the inner parts of Beijing (491–126 μg m −3 ) compared to areas outside the 5th Ring Road (488–203 μg m −3 ). There is parallel evidence of lower emissions from fireworks reflected in decreasing sales, 95 to 2.9 myriaboxes from 2011 to 2019 and lower accumulation of firework debris after the celebrations. Posts to SinaWeibo hint at a growing support for reduced firework use among Beijing's netizens, so consumer perceptions have moved to give more support to regulation. There is also positive commentary on social media about the resultant healthier environment. Official posts stress the need for care with fireworks and note enhanced vigilance over illegal sales fireworks. Although top-down, the approach seems to have met with some success in reducing pollution from fireworks in Beijing. Graphical abstract: Image 1 Highlights: Spikes of PM2.5 at New Year are declining, but less so beyond 5th Ring Road. Inversions determine PM2.5 variability because emissions change only gradually. Firework sales and debris at New Year have decreased over the last decade. Some netizens accept firework restrictions lead to improved health and environment.